Determining Factors for Students' Decision to Choose Private Islamic Religious Universities: The Role of Word of Mouth and Brand Image - Siswanto, Iwan; Silahudin, Agus; Siregar, Kardina Engelina; Eriani, Eva (El-Idare: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to analyze the influence of word of mouth and brand image on students' decisions in choosing a university at the Imam Syafii Islamic Religious Institute (IMSYA) Indonesia. This study uses a quantitative approach with a type of causal associative research. The population in this study is all students in the first semester of the 2025/2026 batch which totals 456 students, with a sample of 213 respondents determined using the Slovin formula. The data collection technique was carried out through a questionnaire with a Likert scale, which has been tested for validity and reliability. Data analysis used prerequisite tests, F tests, and determination coefficients with the help of SPSS. The results of the study show that word of mouth and brand image partially or simultaneously have a significant effect on students' decisions in choosing higher education. Brand image has a more dominant influence than word of mouth. Overall, both variables make a considerable contribution in explaining student decisions. These findings show that positive social communication and a strong institutional image, especially based on religious values, are important factors in increasing student interest, even in relatively newly developed universities.